2005
DOI: 10.1159/000085059
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Mechanisms of Sairei-to on Mesangial Matrix Expansion in Rat Mesangioproliferative Glomerulonephritis

Abstract: Background: Sairei-to (TJ-114) is a Japanese herbal medicine of standardized quality, originating from traditional Chinese medicine. In the present in vivo study, we investigated the suppressive effects of TJ-114 and related drugs, Shosaiko-to (TJ-9), and Saiboku-to (TJ-96), on mesangioproliferative glomerulonephritis (MsPGN) in rats. TJ-9 is a basal prescription of TJ-96 and TJ-114. We evaluated the efficacy of these drugs on proteinuria, extracellular matrix (ECM) accumulation, and superoxide dismutase (SOD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…We have previously observed that sairei-to treatment restored tissue SOD activity in experimental MsPGN [13]. In agreement with the previous results, plasma SOD activity was also restored by sairei-to treatment in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have previously observed that sairei-to treatment restored tissue SOD activity in experimental MsPGN [13]. In agreement with the previous results, plasma SOD activity was also restored by sairei-to treatment in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we have observed that sairei-to had suppressive effects on matrix expansion through the inhibition of macrophage infiltration and the recovery of superoxide dismutase (SOD) activity [13]. Suga et al [14] and Ishii et al [15] reported that an experimental model in rats or mice of peritoneal fibrosis through peritoneal injection of chlorhexidine gluconate (CG) resembled human peritoneal fibrosis in a peritoneal dialysis procedure: increased expressions of collagen, α-smooth muscle actin, and macrophage infiltration were noted in this experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…Macromolecular immune complexes are formed in situ and deposited in the mesangial area, leading to mesangial cell proliferation and inflammation [4, 5]. These inflammatory mediators in turn stimulate activation, shrinkage, and proliferation of mesangial cells; release a variety of inflammatory mediators and ECM components [6, 7]; and aggravate inflammation, all of which result in glomerular damages, including damage to the molecular barrier and charge barrier of the filtration membrane, and proteinuria [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previously we have observed the recovery of tissue SODlike activity by saireito treatment in experimental MsPGN without uninephrectomy, 12) and it was suggested that flavonoids, including baicalin, partly suppressed experimental glomerular and peritoneal fibrosis by anti-oxidative effects. 12,21) However, the Thy-1 model without uninephrectomy recovers one month after the induction of glomerulonephritis and is considered an acute mesangioproliferative model.…”
Section: Discussionmentioning
confidence: 90%
“…12,21) However, the Thy-1 model without uninephrectomy recovers one month after the induction of glomerulonephritis and is considered an acute mesangioproliferative model. 22) In a preliminary experiment using irreversible Thy-1 nephritis, saireito suppressed mesangial cell proliferation, but not azotemia (data not shown).…”
Section: Discussionmentioning
confidence: 99%